Pengaruh Literasi Keuangan dan Sosialisasi Orang Tua Terhadap Minat Menabung di Bank pada Mahasiswa Prodi Manajemen, Universitas Bina Sarana Informatika - Wiwit Rohaeni Yulianti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to determine and analyze the effect of financial literacy and parental socialization both simultaneously and partially on the interest in saving at the Bank in students of the Management Study Program of Bina Sarana Informatika University. This research method uses a quantitative approach with multiple linear regression analysis techniques processed using SPSS version 25. The data collection technique is by distributing questionnaires to 100 students as respondents through google forms. The results showed that financial literacy and parental socialization had a significant influence on interest in saving at the Bank. Simultaneously, financial literacy and parental socialization have a positive and significant effect on the interest in saving at the Bank in Management study program students of Bina Sarana Informatika University.